The survival outcome of patients with relapsed/refractory peripheral T‐cell lymphoma‐not otherwise specified and angioimmunoblastic T‐cell lymphoma. (16th December 2016) - Chihara, Dai; Fanale, Michelle A.; Miranda, Roberto N.; Noorani, Mansoor; Westin, Jason R.; Nastoupil, Loretta J.; Hagemeister, Fredrick B.; Fayad, Luis E.; Romaguera, Jorge E.; Samaniego, Felipe; Turturro, Francesco; Lee, Hun J.; et al.
Summary: Survival outcome of patients with peripheral T‐cell lymphoma‐not otherwise specified (PTCL‐NOS) and angioimmunoblastic T‐cell lymphoma (AITL) who experience disease progression/relapse remains very poor. A total of 321 patients, newly diagnosed with PTCL‐NOS ( n = 180) or AITL ( n = 141) between 1999 and 2015, were analysed. Failure‐free survival (FFS) and overall survival (OS) were calculated from the time of first disease progression (FFS1, OS1), from second disease progression (FFS2, OS2) and from third progression (FFS3, OS3). With a median follow‐up duration of 52 months, 240 patients (135 PTCL‐NOS, 105 AITL) experienced progression/relapse. In patients with PTCL‐NOS, the median durations of FFS1, FFS2 and FFS3 were 3·1, 2·5 and 2·1 months, respectively. In patients with AITL, they were 5·5, 2·9 and 2·3 months, respectively. There was no improvement in FFS1 and OS1 by the time of recurrence during this period (1999–2004, 2005–2009 and 2010–2015). The median FFS after pralatrexate and romidepsin was only 3·0 and 2·5 months, respectively. The 5‐year OS rates after salvage autologous and allogeneic transplant were 32% and 52%, respectively; while the 5‐year OS rates for patients who did not undergo transplant was 10%. Further research for novel therapeutic approaches with higher efficacy and better safety profile are needed.